Pengaruh Literasi Keuangan dan Persepsi Financial Freedom Terhadap Pengambilan Keputusan Investasi Saham Di Pasar Modal Pada Mahasiswa KSPM Universitas Jambi - Lisnawati, Dita; Syuhada, Siti; Putra, Iwan (Jurusan Pendidikan IPS FKIP UNJA, 2023)
:Â This study aims to determine the effect between variables, namely regarding the Effect of Financial Literacy and Perceptions of Financial Freedom on Stock Investment Decision Making in the Capital Market in KSPM University Jambi Students. This research is a quantitative study, the population and sample in this study were student members of the Jambi University KSPM 2019 - 2021. The research data was obtained by distributing questionnaires to Jambi University KSPM students. The data analysis technique used is multiple linear regression analysis with the help of the SPSS 25.0 for windows program. The results of the study show that partially financial literacy (X1) influences stock investment decision making in the capital market (Y) with tcount > ttable 5.517 > 1.661 and partially the perception of financial freedom (X2) also influences stock investment decision making in the capital market (Y) with tcount > ttable, namely 5.288 > 1.661. Simultaneously financial literacy (X1) and perceptions of financial freedom (X2) have a significant effect on stock investment decision making in the capital market (Y) with fcount > ftable, namely 19.987 > 3.09. The Adjust R Square figure is 0.301 or 30.1%. This shows that the percentage contribution of the financial literacy variable (X1) and the perception of financial freedom (X2) on stock investment decision making in the capital market (Y) is 0.301 or 30.1%. Â